2011
DOI: 10.3109/14756366.2011.636360
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase-dependent and -independent mechanisms of reported inhibitors of reactive oxygen generation

Abstract: NADPH oxidase isoform-2 (NOX2) generates reactive oxygen species (ROS) that contribute to neurodegenerative and cardiovascular pathologies. However, validation of NOX2 as a pharmacotherapeutic target has been hampered by a lack of mechanistically-defined inhibitors. Using cellular and biochemical assays, we explored previously reported inhibitors of ROS production (perhexiline, suramin, VAS2870 and two Shionogi patent compounds) as direct NOX2 inhibitors. All but suramin, which presumably lacks cell penetrance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 49 publications
4
49
1
Order By: Relevance
“…Among other NOX inhibitors tested in this study, only DPI, celastrol, and suramin showed inhibition across the cellfree assays independently of assay format, in agreement with previous reports suggesting that DPI is an irreversible inhibitor of NOX2 (14), that celastrol inhibits NOX2 directly and via binding to the p47 phox subunit (30), and that suramin also acts via binding to the NADPH binding site (21). While DPI and celastrol also demonstrated inhibitory activity in the cell-based assays, suramin was not active, perhaps due to lack of cell penetrance as has previously been suggested (60).…”
supporting
confidence: 92%
“…Among other NOX inhibitors tested in this study, only DPI, celastrol, and suramin showed inhibition across the cellfree assays independently of assay format, in agreement with previous reports suggesting that DPI is an irreversible inhibitor of NOX2 (14), that celastrol inhibits NOX2 directly and via binding to the p47 phox subunit (30), and that suramin also acts via binding to the NADPH binding site (21). While DPI and celastrol also demonstrated inhibitory activity in the cell-based assays, suramin was not active, perhaps due to lack of cell penetrance as has previously been suggested (60).…”
supporting
confidence: 92%
“…In a neutrophil-cell-free system, VAS2870 inhibited superoxide production with an IC 50 of 10.6 lM. These results appear inconsistent with findings from Gatto et al who reported lack of inhibition of Nox2 by VAS2870 in a semipurified enzyme preparation (58). This difference may be a consequence of the dynamics of complex assembly that is dependent on the order of addition of the stimulus.…”
contrasting
confidence: 70%
“…Additional effects of perhexiline include blockade of the NAD(P)H oxidase 2 (Nox2) complex, conveying beneficial anti-inflammatory effects (Gatto, et al, 2013;Kennedy, et al, 2006;Liberts, et al, 2007), and reduced expression of TXNIP (Ngo, et al, 2011). Moreover, a recent study reports that perhexiline activates Krüppel-like factor 14 (KLF14), which regulates lipid metabolism, reducing atherosclerotic lesion development in a mouse model .…”
Section: Carnitine Palmitoyltransferase 1 (Cpt1) Inhibitionmentioning
confidence: 99%